The Future of Arms Control - Levi, Michael A. (Book collections on Project MUSE., 2005)
"Lays out the framework of an enduring and effective arms control strategy that is explicitly linked to broader U.S. security policy, focusing on preventing the spread of nuclear and biological arms to extremist states and terrorist organizations"--Provided by publisher.